PENGARUH MEDIA PEMBELAJARAN BUILDING INFORMATION MODELLING (BIM) PADA MATAKULIAH GAMBAR TEKNIK II - Rifyal Ahmad Sunardi (Jurnal Salome : Multidisipliner Keilmuan, 2024)
Building Information Modeling (BIM) is a process that involves creating and managing digital representations of the physical and functional characteristics of buildings. BIM is not just software but also a methodology that enables architects, engineers, contractors and building owners to work more effectively with integrated digital models. The purpose of writing this article is to evaluate the impact of using BIM (Building Information Modeling) learning media on student learning outcomes and interest in studying the Engineering Drawing II course, especially planning drawings, in the Department of Building Engineering and Civil Engineering Education. BIM learning media was chosen to increase students' interest in learning in this department, who previously used standard media such as Excel for calculating financing plans and simple building structures, as well as AutoCAD for engineering drawings with software. It is hoped that this research can help students think applicatively in projects that are used as learning materials. The method used is Literature Review, with a focus on reviewing 20 journals that are relevant to the title of this article.